2018
DOI: 10.2134/jeq2017.10.0407
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorus Sorption to Aluminum‐based Water Treatment Residuals Reacted with Dairy Wastewater: 2. X‐Ray Absorption Spectroscopy

Abstract: Phosphorus capture from wastewater can decrease water pollution and provide a P-rich fertilizer alternative for use in agricultural production. This study was conducted to elucidate P retention mechanisms in Al-based water treatment residuals (Al-WTR) to gain insight regarding P sorption and the potential for P release from Al-WTR after reaction with dairy wastewater. Synchrotron-based microfocused X-ray fluorescence (micro-XRF) spectrometry, bulk P -edge X-ray absorption near edge structure spectroscopy (XANE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 33 publications
(69 reference statements)
1
11
0
Order By: Relevance
“…In the current publication, we present the detection of P distribution onto the materials and identification of its associations with the major constituents (Al, Ca, C, and Si) using advanced SEM‐EDS. In the accompanying publication by Massey et al (2018), we present specific forms of P bound to Al and Ca, complementing the SEM‐EDS findings.…”
supporting
confidence: 53%
See 2 more Smart Citations
“…In the current publication, we present the detection of P distribution onto the materials and identification of its associations with the major constituents (Al, Ca, C, and Si) using advanced SEM‐EDS. In the accompanying publication by Massey et al (2018), we present specific forms of P bound to Al and Ca, complementing the SEM‐EDS findings.…”
supporting
confidence: 53%
“…The SEM‐EDS results in the current study indicated that the usually scattered P had high affinity for Al surfaces but also demonstrated scattered P associated with Ca areas. Phosphorus adsorption to Al and to Ca in both the Al‐WTR and the WW‐Al/O‐WTR was identified by the micro‐X‐ray fluorescence (XRF) P and P K‐edge X‐ray absorption near‐edge structure (XANES) analyses (Massey et al, 2018). These findings are in contrast with those of Bertrand et al (2001) and Makris et al (2004), which suggested that P adsorption is exclusive to Al surfaces.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ajiboye et al (2007) used NMR spectroscopy, chemical extractions, and P K ‐edge XANES analysis to quantify P speciation in organic soil amendments such as manure and biosolids. Similarly, Zohar et al (2018) and Massey et al (2018) combined chemical extractions, scanning electron microscopy with energy dispersive X‐ray spectroscopy (SEM‐EDS), and XANES spectroscopy to quantify speciation in P recovered from wastewater using a mixed Al oxide–calcite sorbent.…”
Section: Discussionmentioning
confidence: 99%
“…Data were collected and analyzed as described above for soils from the producer fields. Since bulk XANES spectroscopy may not always detect minor components, as demonstrated in Massey et al (2018), microfocused X‐ray fluorescence mapping and microfocused P K ‐edge XANES (micro‐XANES) were also performed at Stanford Synchrotron Radiation Lightsource Beamline 14‐3. Samples were encased in optical epoxy (Epotek 301‐2FL), cut to expose soil grains, and lightly polished before analysis.…”
Section: Methodsmentioning
confidence: 99%